Effect of Supplementing Seaweed Extracts to Pigs until d35 Post-Weaning on Performance and Aspects of Intestinal Health - Vigors, Stafford (Mar Drugs, 2021)
The objective of this study was to examine the effects of feeding laminarin (LAM) and fucoidan (FUC) enriched seaweed extracts up to d35 post-weaning on measures of animal performance, intestinal microbial and transcriptome profiles. 75 pigs were assigned to one of three groups: (1) basal diet; (2) basal diet + 250 ppm fucoidan; (3) basal diet + 300 ppm laminarin with 7 replicates per treatment group. Measures of performance were collected weekly and animals sacrificed on d35 post-weaning for the sampling of gastrointestinal tissue and digesta. Animal performance was similar between the basal group and the groups supplemented with FUC and LAM (P > 0.05). Pigs fed the basal diet had higher alpha diversity compared to both the LAM and FUC supplemented pigs (P < 0.05). Supplementation with LAM and FUC increased the production of butyric acid compared to basal fed pigs (P < 0.05). At genus level pigs fed the LAM supplemented diet had the greatest abundance of Faecalbacterium, Roseburia and the lowest Campylobacter of the three experimental treatments (P < 0.05). While neither extract had beneficial effects on animal performance, LAM supplementation had a positive influence on intestinal health through alterations in the gastrointestinal microbiome and increased butyrate production.